Extended Range of a Gun Launched Smart Projectile Using Controllable Canards - Mark Costello (Shock and Vibration)
This effort investigates the extent to which moveable canards can extend the range of indirect fire munitions using both projectile body and canard lift. Implications on terminal velocity and time of flight using this mechanism to extend range are examined for various canard configurations. Performance predictions are conducted using a six-degree-of-freedom simulation model that has previously been validated against range data. The projectile dynamic equations are formed in the body frame and aerodynamic loads from the body and canards are Mach number and angle of attack dependent. The projectile body aerodynamic moments include unsteady aerodynamic damping. The focus of the study is directed toward low cost competent munitions that extend range and as such a simple flight control system is considered which utilizes only timer, roll rate, and roll attitude inputs.